Effect of the Processing and Storage of Thrombocyte Concentrate on the Acidity (Ph) Levels and the Amount of Platerombocites - Muhamad Syamsul Arif Setiyo Negoro (Jurnal Biosains Pascasarjana, 2023)
In order to maintain good quality of trombho concentrate (TC)  based on pH level and platelet count, to store it at 22 ± 2°C for 3 – 5 days in vitro. is to determine the effect of the processing and shelf life of platelet concentrate on pH levels and platelet counts. The research design was quasi-experiment pre and posttest group design.. there was no significant decrease in the pH level of the TC which was processed from whole blood. The  pH level of the TC which was processed from thrombopheresis experienced a significant increase in p value of 0.00. There was a significant increase in the number of platelets in the TC which was processed from whole blood, whereas in the TC which was processed from thrombopheresis it decreased significantly. that the shelf life and the processing of platelet concentrates affect the pH level and the number of platelets